2019
DOI: 10.3390/medicina55050196
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cardiorespiratory Capacity on the Acute Effects of Caffeine on Autonomic Recovery

Abstract: Background and objectives: As a result of ergogenic properties, caffeine has been increasingly taken prior to physical exercise, yet its effects on post-exercise recovery, considering the differences in the cardiorespiratory capacity of the individuals, has not yet been studied or fully elucidated. Optimizing the post-exercise recovery can convey advantages to physical activity practitioners. We evaluated the acute effects of caffeine on heart rate (HR) autonomic control recovery following moderate aerobic exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 31 publications
4
26
0
2
Order By: Relevance
“…When the subjects were ingested avocado pulp, SBP recovered after 2 min following exercise and HR returned after 10 min after exercise termination, while in the placebo protocol, SBP recovered after 3 min following exercise cessation and HR recovered after 20 min of recovery. The abovementioned findings are in accordance with Dzeufiet et al 41 , who studied animals treated with aqueous avocado extract (50, 100 and 150 mg/kg) for five weeks. Their results confirmed that aqueous avocado extract dose-dependently reduced HR and blood pressure of ethanol-sucrose induced hypertensive rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When the subjects were ingested avocado pulp, SBP recovered after 2 min following exercise and HR returned after 10 min after exercise termination, while in the placebo protocol, SBP recovered after 3 min following exercise cessation and HR recovered after 20 min of recovery. The abovementioned findings are in accordance with Dzeufiet et al 41 , who studied animals treated with aqueous avocado extract (50, 100 and 150 mg/kg) for five weeks. Their results confirmed that aqueous avocado extract dose-dependently reduced HR and blood pressure of ethanol-sucrose induced hypertensive rats.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have intended to evaluate the cardioprotective effect of avocado 19,41,42 . The aforesaid references demonstrated the valuable influences of avocado fruit, avocado oil or avocado extract.…”
Section: Discussionmentioning
confidence: 99%
“…After exercise cessation, a temporary decline in SBP below pre-exercise levels is as a result of peripheral vasodilation 32 . www.nature.com/scientificreports www.nature.com/scientificreports/ HR during exercise is controlled by neural and peripheral mechanisms (mechanoreceptors and/or metaboreceptors) 29,30 . Muscle metaboreceptors are activated in response to accumulation of metabolites (H+, K+, adenosine, lactate), decreasing baroreflex sensitivity [33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…The HR, RR, SBP, and DBP data were logged at the 15 th minute of the initial rest and at 1 st , 3 rd , 5 th , 7 th , 10 th , 20 th , 30 th , 40 th , 50 th and 60 th minutes after exercise (Fig. 2) [27][28][29] .…”
Section: Methods Strobe Guidelines Our Investigation Is In Accordancementioning
confidence: 99%
“…However, research ndings are mixed, with some studies showing that 300-400 mg of caffeine delays post-exercise parasympathetic reactivation (12,14,15), while others have found no effect from caffeine at doses associated with <3 mg•kg -1 body mass (16,17). While it is di cult to compare and contrast results across studies, these inconsistent ndings may be related to the caffeine dosage used, which warrants further investigation within athletic populations.…”
Section: Introductionmentioning
confidence: 99%